Functional Zoning for Integrated Management of Transboundary Lake Basins from a Sustainable Development Perspective: A Case Study of Lake Victoria in East Africa. - Jin, Shiying; Zhang, Xinxin; Wang, Mengyuan; Kishe, Mary A.; Gao, Qun; Liu, Qianqian (Environmental Management, 2025)
From the perspective of sustainable development, multi-objective collaborative governance plays a vital role in the integrated management of transboundary lake basin systems. However, regionally differentiated governance solutions, based on the systematic identification of spatial use functions within the basin, remain undefined. Based on an analysis of regional evolution patterns, this study establishes a coupled zoning framework to identify conflict types and synergetic relationships while quantifying the characteristics of the three spatial use functions: agricultural production, urban development, and ecological conservation. The results of applying this framework in the Lake Victoria Basin (LVB) show that between 2010 and 2020, agricultural production and urban development across the basin increased, while ecological conservation in the northwestern catchment significantly declined. Advantageous functional areas displayed strong spatial heterogeneity, and sub-functions within composite advantageous functional areas predominantly exhibited low-level positive synergy. Finally, by integrating conflict and synergy through cross-benefit linkages, the study area was refined into six zoning categories with clear distinctions. This study proposes a basin management zoning framework aimed at optimizing management strategies by identifying functional conflicts and bridging gaps in international transboundary basin governance research.